Fibre discrimination by various tests and analytical techniques - Gina Francesca Gabriel; Nor Salwana Mahassan; Pua, Hiang; Noor Hazfalinda Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2019)
Fibres are important trace evidence that can be found during the course of crime scene investigation. The identification and analysis of these fibres shed light as to the circumstances surrounding a particular crime. Identifying the factors that affect the transference of fibres under various environments are crucial in providing robust conclusions of a case per se, as highlighted in this work. Donor garments were made up of four different types of fibre; 100% cotton, 100% nylon, 100% polyester and 100% wool, that were used to observe the differences in the number of transferred fibres to the recipient garment (100% cotton) and vice versa with increasing contact times of 30, 60, 180, and 300 seconds respectively. To simulate contact between the donor garment worn by a suspect and the recipient garment worn by a victim in real-life situations, the donor garment was placed on top of the recipient garment which was laid on a piece of plywood. The numbers of transferred fibres, both from the donor to the recipient garment and from the recipient to the donor garment were observed and tested using microscopic examination, burning test, solubility test and dye extractability test. Results indicated that different types of garments transferred different number of fibres with increasing contact times, and the identification of the fibres are possible via the different tests applied in this work.